Sigma-delta modulator: loop filters and quantization noise - Golub, V. S. (Technology and design in electronic equipment, 2013)
In this paper the sigma-delta modulator was analyzed with the use of simulation. In particular, the author studied dependence of the quantization noise on the loop filtration. The obtained results explain certain operation features of the modulator and make it possible to give advice as to its application.